The Baecke Habitual Physical Activity Questionnaire (BHPAQ): a valid internal structure of the instrument to assess healthy Brazilian adults - Rocha,Daniel Santos (2022)
SUMMARY OBJECTIVE: This study aimed to validate the internal structure of the Brazilian version of the Baecke Habitual Physical Activity Questionnaire. METHODS: A cross-sectional study was conducted with individuals over 18 years old of both sexes, with Brazilian Portuguese as their native language. The structure of the Baecke Habitual Physical Activity Questionnaire was tested by confirmatory factor analysis. The model fit was evaluated by the following indices: root mean square error of approximation, comparative fit index, Tucker-Lewis index, standardized root mean square residual, and χ²/degrees of freedom. We used the Akaike information criterion and Bayesian information criterion to compare different structures of the Baecke Habitual Physical Activity Questionnaire. RESULTS: A total of 241 individuals participated in this study. The original structure of the Baecke Habitual Physical Activity Questionnaire with 16 items and 3 domains was compared to a structure with 14 items and 3 domains. The internal structure of the Baecke Habitual Physical Activity Questionnaire with 14 items showed better fit indices and lower Akaike information criterion and Bayesian information criterion values. CONCLUSION: The best internal structure of the Brazilian version of the Baecke Habitual Physical Activity Questionnaire in adults presents 3 domains and 14 items.